Predictors of Time to Death After Terminal Withdrawal of Mechanical Ventilation in the ICU - Cooke, Colin R. (American College of Chest Physicians, 2010)
BACKGROUND: Little information exists about the expected time to death after terminal withdrawal of mechanical ventilation. We sought to determine the independent predictors of time to death after withdrawal of mechanical ventilation. METHODS: We conducted a secondary analysis from a cluster randomized trial of an end-of-life care intervention. We studied 1,505 adult patients in 14 hospitals in Washington State who died within or shortly after discharge from an ICU following terminal withdrawal of mechanical ventilation (August 2003 to February 2008). Time to death and its predictors were abstracted from the patients’ charts and death certificates. Predictors included demographics, proxies of severity of illness, life-sustaining therapies, and International Classification of Diseases, 9th ed., Clinical Modification codes. RESULTS: The median (interquartile range [IQR]) age of the cohort was 71 years (58-80 years), and 44% were women. The median (IQR) time to death after withdrawal of ventilation was 0.93 hours (0.25-5.5 hours). Using Cox regression, the independent predictors of a shorter time to death were nonwhite race (hazard ratio [HR], 1.17; 95% CI, 1.01-1.35), number of organ failures (per-organ HR, 1.11; 95% CI, 1.04-1.19), vasopressors (HR, 1.67; 95% CI, 1.49-1.88), IV fluids (HR, 1.16; 95% CI, 1.01-1.32), and surgical vs medical service (HR, 1.29; 95% CI, 1.06-1.56). Predictors of longer time to death were older age (per-decade HR, 0.95; 95% CI, 0.90-0.99) and female sex (HR, 0.86; 95% CI, 0.77-0.97). CONCLUSIONS: Time to death after withdrawal of mechanical ventilation varies widely, yet the majority of patients die within 24 hours. Subsequent validation of these predictors may help to inform family counseling at the end of life.